Parents’ Perceptions on Menstruation and Menstrual Hygiene in Kinshasa, Democratic Republic of Congo - Nsakala , Gabriel Vodiena; Mpembele, Blondelle Ntadisa (International Journal of Health Sciences, 2025)
Purpose: Effective management of menstrual hygiene is crucial for women’s sexual and reproductive health. This study aimed to assess parents’ perceptions of adolescent menstruation and menstrual hygiene within households in the Kimbanseke health zone in Kinshasa. Methodology: This exploratory, descriptive, thematic, and interpretive study utilized semi-structured interviews with 6 mothers and 6 fathers in the zone. Findings: The findings revealed that menstruation remains a taboo subject within the community of Kimbanseke, with its management often shrouded in secrecy in many of the surveyed households. The factors significantly influencing women’s menstrual health were largely societal in nature. Both mothers and fathers reported being aware of various beliefs and myths surrounding menstruation. These beliefs were subsequently passed down to their children, perpetuating silence and reinforcing taboos about menstruation. Unique Contribution to Theory, Policy and Practice: There is a clear need to integrate parental education and training into policies aimed at promoting menstrual hygiene. Parents play a critical role in shaping their daughters' behaviors and practices concerning menstruation and menstrual hygiene, making their involvement essential to improving menstrual health education.